Math

posted by .

integrate (sinx)^(5)(cosx)^(12)from 0 to (pi/2)

I'm having problems just even integrating it...
I tried breaking it up
(sin^(2)x)^(2)(cos^(2)x)^(6)(sinx)dx
then doing u-sub with u=cosx and du= -sinx
but then I get stuck...
the answer is 8/3315 just don't know how to get that answer!

• Math -

When you have products of powers of sin and cos, look to see if one of the has odd power and the other one is even (as in this case).

This being the case, you can use reduce the odd power to even by combining it with the dx, and reduce the rest (all even power) to powers of either only sine or only cosine.

I=∫sin^5(x)cos^12(x)dx
=∫sin^4(x)cos^12(x) sin(x)dx
=∫ (1-sin²(x))²cos^12(x) sin(x)dx

Use substitution u=cos(x), du=-sin(x)dx

I=-∫(1-u²)²u^12du
=-∫(u^12-2u^14+u^16)du
=-(u^13/13-2u^15/15+u^17/17)] from u=cos(0) to u=cos(π/2)
= 8/3315

Similar Questions

1. Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
2. Simplifying with Trigonometry Identities

Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each other. …
3. Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
4. Trig........

I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
5. Math - Pre- Clac

Prove that each of these equations is an identity. A) (1 + sinx + cos x)/(1 + sinx + cosx)=(1 + cosx)/sinx B) (1 + sinx + cosx)/(1 - sinx + cosx)= (1 + sin x)/cosx Please and thankyou!
6. Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] = [cosx(1-sinx]/[cosx(1+tanx] …
7. trigonometry

can i use factoring to simplify this trig identity?
8. Trigonometry

Prove the following trigonometric identities. please give a detailed answer because I don't understand this at all. a. sin(x)tan(x)=cos(x)/cot^2 (x) b. (1+tanx)^2=sec^2 (x)+2tan(x) c. 1/sin(x) + 1/cos(x) = (cosx+sinx)(secx)(cscx) d. …
9. Calculus 2 Trigonometric Substitution

I'm working this problem: ∫ [1-tan^2 (x)] / [sec^2 (x)] dx ∫(1/secx)-[(sin^2x/cos^2x)/(1/cosx) ∫cosx-sinx(sinx/cosx) ∫cosx-∫sin^2(x)/cosx sinx-∫(1-cos^2(x))/cosx sinx-∫(1/cosx)-cosx sinx-∫secx-∫cosx …
10. Trigonometry

How do you simplify: (1/(sin^2x-cos^2x))-(2/cosx-sinx)?

More Similar Questions